Sea-water Yagi antenna design - Wu, Heying (2019)
This project is to study, design and fabricate a reconfigurable sea-water Yagi monopole antenna with one driven elements, a director element and a reflector element. In a previous study of sea-water Yagi monopole antenna, it is designed with one driven element and a parasitic element. Both simulated result and experimental result have proven an antenna which is based on sea-water is workable and with high applicable value. In this paper, an extra element will be introduced to the project. The new design is analyzed, simulated, fabricated and in lab experiment with improved performance. Ansoft HFSS is used to analyze and simulate the 3D design model and obtain the theoretical result before experiment. 3D printing technology has been used to fabricate the model and makes it more accurate to the software designed model. The new antenna design of a driven element with two parasitic elements showing the similar directivity with the model of one driven element and one director. But the prototype is to be modified with a higher gain performance in the future.